Bentuk Penyajian Tari Kerajaan Pelalawan di Sanggar Bina Tasik Kabupaten Pelalawan Provinsi Riau - Dea Larisa; Yahyar Erawati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The title of this research is "Presentation Form of Pelalawan Kingdom Dance at the Bina Tasik Studio, Pelalawan Regency, Riau Province". This study aims to determine the form of presentation of Pelalawan Kingdom dance at the Bina Tasik Studio, Pelalawan Regency, Riau Province. Pada penelitian ini peneliti menggunakan metode kualitatif deskriptif. In this study, the researcher used a descriptive qualitative method. The data collection techniques used were observation, interviews and documentation. The results of this study indicate that the Pelalawan Kingdom dance uses dance movements with 5 basic dance movements, namely the salute movement, the Pangean silat movement, the rowing movement, the circular movement, and the last is the final movement. The musical instruments used to accompany the Pelalawan Kingdom dance are the long drum, kompang, gong, calempong, drum, violin, accordion and darmuka. The title of this dance is taken from a historical story about the Pelalawan Kingdom. The theme of the dance is about the feud or war between the Portuguese and the Malacca Kingdom which resulted in the Malacca Kingdom being destroyed and a new kingdom being born, namely the Pelalawan Kingdom. The type of dance is classified as a new creative dance type. The presentation mode is symbolic representational dance. The number of dancers is 11 dancers, of which 5 are male dancers and 6 are female dancers. The women's dance costume uses the kebaya tabuh shirt and the men's costume uses the Malay cekak musang shirt. The makeup of the female dancers uses beautiful makeup while the makeup of the male dancers only uses powder and eyebrows. Lighting but because this dance is danced during the day and the stage is outside the field, no light is needed. Dance properties are the door and wall of Pekan Tua, the door and wall of Pelalawan, keris and shawl. The audience was attended by school residents and invited guests.